2002
DOI: 10.1111/j.1744-7429.2002.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Distress Calls of Birds in a Neotropical Cloud Forest1

Abstract: Distress calls are loud, harsh calls given by some species of birds when they are captured by a predator or handled by humans. We recorded the frequency of distress calls and struggling behavior in 40 species of birds captured in mist nets during the dry season in a Costa Rica cloud forest. We tested the following hypotheses proposed to explain the function of distress calls: (1) calling for help from kin or reciprocal altruists; (2) warning kin; (3) eliciting mobbing behavior; (4) startling the predator; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…We found that about 21 % of parrotbills gave screaming calls while being handled. It is interesting to note that this proportion of callers is similar to previous results that showed a positive relationship between body mass and scream tendency in birds (Neudorf and Sealy 2002). Overall, individual morphology and flock size were not associated with screaming behavior, but females tended to scream more than males in this species.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We found that about 21 % of parrotbills gave screaming calls while being handled. It is interesting to note that this proportion of callers is similar to previous results that showed a positive relationship between body mass and scream tendency in birds (Neudorf and Sealy 2002). Overall, individual morphology and flock size were not associated with screaming behavior, but females tended to scream more than males in this species.…”
Section: Discussionsupporting
confidence: 87%
“…He argued that this is adaptive because captured prey scream to attract other individuals that are able to disturb the original predators (e.g., conspecifics, secondary predator), and in closed habitats where visual cues of predation are relatively limited, acoustic cues will be used by captured prey to announce their desperate situation. However, such habitat differences in the tendency to scream could be confounded by other biological factors; for example, the tendency to scream tended to differ markedly between species with different body sizes that live in a similar habitat (Neudorf and Sealy 2002). Nevertheless, this study proved that such effects of habitat type on screaming propensity are valid even in a species inhabiting diverse habitats; parrotbill populations occupying closed habitats screamed significantly more than populations living in open areas, strengthening the view that fear screams may have survival value that differs between habitats.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations